INSTITUIONAL AND LEGAL BASIS OF THE DEVELOPMENT OF THE INTERNATIONAL RELAIONS BETWEEN STATES OF THE CARPATHIAN EUROREGION - Мітряєва, С.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
Analysis of collaboration should begin with the definition of institutional and legal framework. The international legal framework – is the foundation upon which the whole system of foreign relations is built. Neighboring countries of Ukraine ( Carpathian Euroregion partners ) are already members of the EU supranational union , so in addition to the analysis of the power of each of the aforementioned countries , should take into account the capacity of the EU, which creates „additional capacity" for its members.